USING WORD GRID GAMES TO INCREASE THE VOCABULARY ACHIEVEMENT OF THE SECOND GRADE STUDENTS OF SMP N 8 PEKANBARU - Hidayat, Sandi Ade; Gultom, Effendy (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2013)
Vocabulary plays an important role in learning a foreignlanguage. It is an element that links the four language skills: speaking,listening, reading and writing. In order to communicate well in aforeign language, students need to have sufficient vocabulary. Afterthat, they need to understand the structure, function, etc. Toenrichtheirvocabulary.There are many useful approaches can be used. Oneof them is using games.